Avaliação não invasiva da pressão intracraniana no diabetes mellitus tipo 2 e sua relação com a modulação autonômica cardiovascular - Galdino, Gabriela Aguiar Mesquita (Universidade Federal de São Carlos, 2019)
Diabetes mellitus, characterized as metabolic changes promoted by insulin resistance, presents exponential growth of cases every year and can lead to serious complications. The complications most known and leading to high mortality rates mainly involve the cardiovascular system and subsequent cerebrovascular system. The cause related to these damages is concentrated in the increase of circulating glycemia and its toxicity to the wall of the vessels. The evaluation of cardiovascular autonomic nervous system integrity through baroreflex sensitivity is an important tool for the prognosis and evolution of the disease. In addition, impairment in autonomic control may make these individuals more susceptible to the development of arrhythmias and stroke. From this, it is important to understand the influence of cardiovascular autonomic compromise on cerebrovascular responses, through its compliance, to propose strategies for the control and prevention of complications. In this context, we proposed a project (Study I) entitled "Noninvasive intracranial pressure and its relationship with autonomic cardiovascular modulation in type 2 diabetes mellitus". Seventeen individuals with type 2 diabetes mellitus without cardiovascular autonomic neuropathy (CAN) and seventeen healthy subjects, male, 40-64 years, were evaluated. Evaluations consisted of tests to identify autonomic cardiovascular and sensorimotor neuropathy; assessment of body composition and presence of peripheral arterial disease; active postural change for evaluation of cardiovascular autonomic control and noninvasive assessment of intracranial pressure. Subjects were age- matched, body mass, height and body mass index (p> 0.05) and the mean age groups was 50 ± 6 years. The main findings of this study were: 1) there was no difference between the group with type 2 diabetes mellitus and control group in relation to cerebrovascular compliance i.e., P2 / P1 (p = 0.989); 2) with active postural change, only diabetics presented a significant reduction (p <0.001) (0.93 ± 0.12) in orthostatism in relation to cerebrovascular compliance; 3) with worsened glycated hemoglobin there is a moderate increase in intracranial pressure (r = 0.517, p = 0.032); 4) there was a moderate and negative relation (r = -0.539, p = 0.025) between coherence in the low frequency component and noninvasive intracranial pressure. It is concluded that diabetics have a preserved ability to regulate intracranial pressure, since they are individuals without autonomic cardiovascular and sensorimotor neuropathy. However, the lower disease control leads to increased cerebrovascular resistance. In addition, lower supine cardiovascular coupling suggests worsening intracranial pressure, reinforcing the importance of disease control and tracing strategies to prevent complications in order to improve the condition and quality of life of this population.
Noninvasive evaluation of intracranian pressure in type 2 diabetes mellitus and its relationship to autonomic cardiovascular modulation
Keywords: Diabetes mellitus; Doenças cardiovasculares; Pressão intracraniana; Sensibilidade barorreflexa; Cardiovascular diseases; Intracranial pressure; Baroreflex sensitivity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL